Silicon Carbide Nanoparticle-Enabled Strengthening of Aluminum and Copper Resistance Spot Welds - Vinayagamurthi PONNUSAMY; Ravikumar MUTHAIYAN; Suresh SUBRAMANIAN; Rajamurugan GOVINDASAMY (Medžiagotyra)
Resistance spot welding (RSW) is a widely employed technique for joining aluminum and copper alloys, valued for its efficiency and effectiveness. However, the mechanical properties of the resulting welds, particularly their tensile strength and resistance to deformation, often fall short of industrial demands. This study explores the incorporation of Silicon Carbide nanoparticles (SiC NPs) as a method to enhance the mechanical performance of RSW joints in aluminum and copper alloys. Experimental results demonstrate that the addition of SiC NPs significantly improves tensile strength, with gains primarily attributed to grain refinement and the formation of dispersion-strengthening mechanisms. Advanced characterization techniques, including Field Emission Scanning Electron Microscopy (FESEM) and EDS analysis, provide detailed insights into the morphological and structural transformations within the weld zones. These findings underscore the potential of SiC NPs to not only enhance the strength and durability of RSW joints but also to advance the overall quality and reliability of welding processes in aluminum and copper alloys. This research opens new avenues for the application of nanoparticle reinforcement in industrial welding, offering a pathway to achieve superior joint performance.